A pareto multi-objective optimization approach for solving time-cost-quality tradeoff problems - Diao, Xundi; Li, Heng; Zeng, Saixing; Tam, Vivian Wy; Guo, Hongling (Technological and Economic Development of Economy, 2011)
Speeding up a project's duration will definitely increase the cost and decrease the quality. The previous literatures were mainly related to project planning and controlling which mainly focus on cost-time tradeoff. However, limited researches have been referred to project quality based on mathematical methodologies. This paper proposes a tradeoff problem on time-cost-quality performance. A computer-based Pareto multi-objective optimization approach is utilized for solving the tradeoff problems. The approach can help searching near the reality Pareto-optimal set while not receiving any information on the stakeholders’ preference for time, cost and quality. Based on the developed approach, decision-making can become easy according to the sorted non-dominated solutions and project preferences.